2018
DOI: 10.1016/j.orggeochem.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Depositional environment and hydrocarbon source potential of the Lower Miocene oil shale deposit in the Aleksinac Basin (Serbia)

Abstract: The most prolific oil shale deposit in Serbia is located in the Aleksinac Basin and is assigned to the Lower Miocene. Depositional environments and hydrocarbon potential were assessed for the Aleksinac oil shale and coal layers through bulk geochemical, organic petrographical, biomarker, and carbon isotope data from core samples from a single well. Maturity parameters (vitrinite reflectance, T max , biomarker isomerisation ratios) prove that the organic matter (OM) is immature. A lower lacustrine oil shale seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The depositional environment has significant effects on the composition of shale with different types of kerogen [45,46,[55][56][57]. In addition, for shales with different kerogen types, they have their own relationships between different compositions [34,[58][59][60].…”
Section: Composition Of the Shale Samples With Type III Kerogen Formementioning
confidence: 99%
“…The depositional environment has significant effects on the composition of shale with different types of kerogen [45,46,[55][56][57]. In addition, for shales with different kerogen types, they have their own relationships between different compositions [34,[58][59][60].…”
Section: Composition Of the Shale Samples With Type III Kerogen Formementioning
confidence: 99%
“…Beside their origin from carotenoids specific for photosynthetic green sulphur bacteria (Chlorobiaceae; Summons and Powell, 1987), aryl isoprenoids have been reported as diagentic products from β-carotane by Koopmans et al, (1996). However, the occurrence of β-isorenieratane in the oil shale sample at 77.3 m depth, suggests that the aryl isoprenoids are most probably derived from green sulphur bacteria (Brocks and Schaeffer, 2008;Bechtel et al, 2018).The occurrence Formation. Std., standard (1,1'-binaphthyl).…”
Section: Hopanoidsmentioning
confidence: 99%
“…Many studies of OM accumulation in lacustrine shale suggest that OM-supplemented and depositional environment dominated source rock development. 62,69,70 In the study, the Taiyuan to the Shanxi demonstrated similar OM input with slight variation between the two formations. This was accompanied by a fluctuation of the paleoclimate toward greater humidity (Figure 4).…”
Section: Resultsmentioning
confidence: 70%